A forestry management research study in the Broadleaf Middle-Hill Forest of Nepal - Thompson, I (Oxford Forestry Institute, University of Oxford, 1986)
The forest resource of the middle hills and factors (related to ecology, demand and implementation) which affect the choice of silvicultural options for it are given to provide a context for the description of the trials set up to date as part of the management research programme of the Nepal-UK Silvicultural Research Project. The procedures for the research in Schima Castanopsis forest are given. Results of the initial measurement of the standing crop, its treatment and in one case its remeasurement are given. Silvicultural options examined were simple coppice, coppice-with-standards (one of 40% crown cover of standards, another of 70% crown cover of standards) and high forest. Initial estimates of productivity in these unmanaged forests (see Chapter 5 for description) are as follows: In Nagarkot the wood dry mean annual increment (MAl) was 4.9 t/ha/yr at 5 years. Standing foliage biomass was 2.7 t/ha. In Aushadi the wood dry MAl was 6.5 t/ha/yr a 9 years with 7.5 t/ha standing foliage biomass. It must be stressed that these results are first estimates of yields from particular sites. However in the virtual absence of yield data for the broadleaf forests in the middle hills they may provide a useful indication of potential yields. Some 50-60% of trees in these forests were identified as of fodder value although in a 2-year old forest at Khalti this fell to 30-35% due to the presence of non-fodder pioneer species. Management shows potential for increasing and improving fodder production, improving access and allowing the selection of species for end use but only limited information on the quantity and distribution of yield is available at this early stage. It is concluded that given adequate protection the trials can provide important information on the effects of the different silvicultural options on the quantity and distribution of forest produce which will be of practical benefit to the forest manager.